Relationship between attributional style and learning styles with students in school of Lima Metropolitana - Matalinares Calvet, María (2010)
This study aimed to examine the relationship between attributional style and learning styles of high school students in Metropolitan Lima. We worked with 364 subjects aged 14 to 17 years, of both sexes, 4th and 5th grade of secondary education. Was applied Attributional Style Questionnaire proposed by Alonso (1991) and Alonso and Sánchez (1992) adapted by Matalinares (2009) and the Learning Styles Inventory of Kolb (1979) adapted by Drain (1991). The results showed a relation between attributional styles and learning styles. A significant relation between the areas that make up the experiential learning and attributional styles. There are differences between the attributional styles of men and women in the dimensions of attribution of academic success to ability and in the attribution of failure to lack of skill. Learning styles of men and women differ in the area of active experimentation. Finally, we found that there is a greater preference for allocation to successful relationships and a lower perception of the attribution of failure to the teacher. In the case of attributional styles in the area of interpersonal relationships, they present a preference for the Allocation of the success in interpersonal relations skill, and this is used to a lesser extent the belief of outsourcing failure.